Cross-linguistic and cross-disciplinary investigation of lexical bundles in academic writing - Kashiha, Hadi; Chan, Swee Heng (Universiti Putra Malaysia Press, 2014)
The present paper reviews the use of lexical bundles in academic writing from two different viewpoints namely linguistic and discipline, directed at how academic writers belonging to different disciplines or linguistic backgrounds construct their discourses through lexical bundles. As cohesive devices, lexical bundles are an indispensible part of the text and play a crucial role in shaping propositions, evolving the text, guiding readers through the flow of information and gaining the writer's proffered meaning. By using lexical bundles, academic writers are able to attain naturalness in their writings and create a more reader-friendly approach to the unfolding text. Bearing the significance of lexical bundles in mind, this review paper aims to examine the effect of disciplinary variation and linguistic differences on the use of lexical bundles in academic writing. Most researchers believe that the frequency as well as the use of lexical bundles is different across disciplines and from one language to another language. Therefore, through a review of previous studies, there is a systematic investigation of evidence to support the above claims. Possible limitations of previous studies are discussed and some implications for further research are presented.